2015
DOI: 10.1111/jmft.12116
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Family Therapy Trainees' Reports of Explicit Weight Bias

Abstract: Discrimination based on an individual's weight has been observed in health care, education, retail, and other public sectors (Puhl & Huer, Obesity, 17, 941, 2007). Such inequity, known as "weight bias," generates negative short-term and long-term consequences for the individuals that experience it (Puhl & Brownell, Weight bias in health care settings, 2007). Past research has shown that healthcare trainees exhibit weight bias (Phelan et al., Obesity, 22, 1201, 2014; Wigton & McGaghie, Journal of General Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
3
24
1
Order By: Relevance
“…Similar to previously published research (Pratt et al , 2015b, participants reported a lack of familiarity with the topic of weight bias and the subsequent effects weight bias could have on their clinical encounters. Particular concern was noted about students beginning their clinical work without receiving training on weight bias and working with clients who are overweight.…”
Section: Training Feedbacksupporting
confidence: 78%
See 4 more Smart Citations
“…Similar to previously published research (Pratt et al , 2015b, participants reported a lack of familiarity with the topic of weight bias and the subsequent effects weight bias could have on their clinical encounters. Particular concern was noted about students beginning their clinical work without receiving training on weight bias and working with clients who are overweight.…”
Section: Training Feedbacksupporting
confidence: 78%
“…In 2010, a study reported that approximately 70 % (N = 217) of clinicians polled from the American Association of Marriage and Family Therapy, reported seeing one client for obesity-related challenges in the past year (Lambert-Shute et al 2010). Despite the fact that MFTs are working with this population, a recent study focusing on MFT students, faculty, and clinicians found that participants reported not receiving training on how to effectively work with clients who were overweight on their weight-related behaviors, even though they were treating these clients in practice (Pratt et al , 2015b. Participants in this study believed that clinicians should receive training on how to work with clients who are overweight in an effective and sensitive manner.…”
Section: Clinical Trainingmentioning
confidence: 60%
See 3 more Smart Citations